2016
DOI: 10.1007/s00018-016-2298-7
|View full text |Cite
|
Sign up to set email alerts
|

Axial and limb muscle development: dialogue with the neighbourhood

Abstract: Skeletal muscles are part of the musculoskeletal system which also includes nerves, tendons, connective tissue, bones and blood vessels. Here we review the development of axial and limb muscles in amniotes within the context of their surrounding tissues in vivo. We highlight the reciprocal dialogue mediated by signalling factors between cells of these adjacent tissues and developing muscles and also demonstrate its importance from the onset of muscle cell differentiation well into foetal development. Early emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 153 publications
0
33
0
Order By: Relevance
“…The influence of neural tube, neural crest cells, notochord and ectoderm on the formation of muscles has been previously extensively studied and showed that Shh, BMP, Wnt, FGF, and Notch signaling pathways participate to both axial and limb myogenesis (reviewed in Deries and Thorsteinsdóttir, 2016). …”
Section: Muscle Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of neural tube, neural crest cells, notochord and ectoderm on the formation of muscles has been previously extensively studied and showed that Shh, BMP, Wnt, FGF, and Notch signaling pathways participate to both axial and limb myogenesis (reviewed in Deries and Thorsteinsdóttir, 2016). …”
Section: Muscle Developmentmentioning
confidence: 99%
“…Once they reached their target sites, PAX-3 positive cells proliferate and organize into dorsal and ventral muscle masses. Muscle differentiation is then initiated, followed by muscle mass growth and splitting (reviewed in Duprez, 2002; Deries and Thorsteinsdóttir, 2016). …”
Section: Muscle Developmentmentioning
confidence: 99%
“…A primary (embryonic) myogenesis takes place to generate primary muscle fibers, between embryonic day (E) 9.5 and E14.5 in the mouse. This is followed during fetal stages by a secondary myogenesis which gives rise to the bulk of skeletal-muscle fibers present at birth (Kelly and Zacks, 1969; Biressi et al, 2007; Tajbakhsh, 2009; Deries and Thorsteinsdóttir, 2016). All skeletal-muscle cells have the same underlying functions, although their progenitors within the paraxial mesoderm are spread throughout the embryo at the onset of myogenesis.…”
Section: Prenatal and Adult Myogenesismentioning
confidence: 99%
“…The somite is initially a spherical unit of polarized epitheloid cells that soon after subdivides into two compartments, the ventral mesenchymal sclerotome and the dorsal epithelial dermomyotome. Shortly afterwards, myogenic precursor cells from the epaxial and hypaxial lips of the dermomyotome undergo an epithelial-mesenchymal transition (EMT) and accumulate underneath, where they differentiate and elongate to form the myocytes of the myotome, the first myogenic structure to develop in the body (Buckingham and Relaix, 2015; Deries and Thorsteinsdóttir, 2016). The epaxial region of the myotome gives rise to the deep back muscles, whereas the hypaxial myotome is the source of body wall muscles and most other trunk muscles (Buckingham and Relaix, 2015; Deries and Thorsteinsdóttir, 2016).…”
Section: Prenatal and Adult Myogenesismentioning
confidence: 99%
See 1 more Smart Citation